2019
DOI: 10.1002/asia.201901108
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Corey–Chaykovsky Reaction: Synthesis of Unusual Cyclopropanoids via Desymmetrization and Thereof

Abstract: Desymmetrization-based protocols for the synthesis of highly functionalized indeno-spirocyclopropanes and cyclopropa-fused indanes have been established through unexpectedr eactions triggered by the Corey-Chaykovsky reagent. These structures were further elaborated in one step to privileged scaffolds such as fluorenones, indenones, and naphthaphenones. For instance, an acid-catalyzedt ransformation of indeno-spirocyclopropanes provided fluorenones via ah omo-Nazarov-type cyclization, and naphthaphenones were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…During the course of their study, Ramasastry and co-workers synthesized chiral indanone scaffolds 13 from symmetrical enone compounds 12. 35 This diastereoselective transformation was facilitated by the Corey–Chaykovsky reagent, namely dimethyloxosulfonium methylide (DOSM) through initial Michael addition followed by aldol-type reaction. The indanone containing allylic-benzylic tertiary alcohol moiety 13 could be converted to fluorenone 14 in excellent yields with catalytic amount of p -TSA.…”
Section: Synthesis Of Fused Scaffoldsmentioning
confidence: 99%
“…During the course of their study, Ramasastry and co-workers synthesized chiral indanone scaffolds 13 from symmetrical enone compounds 12. 35 This diastereoselective transformation was facilitated by the Corey–Chaykovsky reagent, namely dimethyloxosulfonium methylide (DOSM) through initial Michael addition followed by aldol-type reaction. The indanone containing allylic-benzylic tertiary alcohol moiety 13 could be converted to fluorenone 14 in excellent yields with catalytic amount of p -TSA.…”
Section: Synthesis Of Fused Scaffoldsmentioning
confidence: 99%
“…Using density functional theory calculations, Yu and colleagues recently reported that these different reaction outcomes can be attributed to thermodynamics, as sulfonium ylide 1a is less stable, and therefore more highly reactive, than sulfoxonium ylide 2a. 4) To date, sulfur ylides 1a and 2a have been widely used in the synthesis of various epoxides, 5,6) cyclopropanes, 7,8) and heterocyclic compounds. [9][10][11] Doubly-activated cyclopropanes are versatile intermediates for the synthesis of a wide range of carbocycles 12) and heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…However, sulfonium ylides used in this reaction were limited to EWG-stabilized ones 1b. Since sulfur ylides with various reactivities have been used in organic synthesis, [5][6][7][8][9][10][11] this study focused on the reaction between different sulfur ylides and spirocyclopropanes. Herein, the ring-opening cyclization of spirocyclopropanes 3 using non-, alkyl-, and phenyl-substituted sulfoxonium ylides 2 as a carbon nucleophile is reported (Chart 2B).…”
Section: Introductionmentioning
confidence: 99%